Post-hatch fasting and infectious bronchitis vaccination affect growth, gastrointestinal development, and morphometric parameters of the small intestine of broiler breeders up to three weeks of age - Fernandez-Alarcon, Miguel Frederico [UNESP]; Souza, Fernando Augusto de [UNESP]; Borges Campos, Daniel Mendes [UNESP]; Hada, Fabricio Hirota [UNESP]; Lima Nogueira, Wedson Carlos; Macari, Marcos [UNESP]; Furlan, Luiz Roberto [UNESP]; Furlan, Renato Luis [UNESP] (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2019)
The influence of fasting and vaccination against infectious bronchitis (IB) on growth, gastrointestinal development, and morphometric parameters of the small intestine of newborn broiler breeders was investigated. Weight gain (WG), feed conversion ratio (FCR), gastrointestinal visceral growth, residual yolk sac, and morphometric parameters of the small intestine were measured in chicks aged up to 21 d. We showed that WG was lowest in chicks exposed to longer fasting periods (72 h), although compensatory gains with increasing age were also observed. Unvaccinated chicks performed better at seven days; however, at 21 d of age, a compensatory response led to better FCR in vaccinated birds. Allometric growth of the gastrointestinal tract was affected following longer fasting periods, but this effect occurred predominantly in younger birds (three days). Compared with non-fasted, birds fasted for 72 h had lower villus height and crypt depth along the small intestine at three days and lower villus height in the duodenum and jejunum at seven days. However, at 14 and 21 days of age, the previous changes in intestinal morphology imposed by fasting had been offset. The IB vaccine, applied in the first day of life, does not affect the allometric growth of the gastrointestinal organs, but causes momentary loss in the intestinal morphometry, which contributes to the reduction of WG at seven days. Our results suggest that long fasting periods after hatching (48 and 72 h) should be avoided in broiler breeders due to the resulting delay in gastrointestinal organ development and growth impairment up to 21 d of life.
Keywords: food restriction; gastrointestinal tract growth; infectious bronchitis immunization; intestinal morphometry